Minimally invasive esophageal surgery-standard of care-our experience - Patnaik, Snigdha; Patnaik, Sujit Chyau (International Journal of Research in Medical Sciences, 2017)
Background: Surgery is the most effective treatment for the resectable esophageal cancer of the middle & lower third and gastro-esophageal junction (GEJ) tumors. We hereby scrutinise our experience in minimally invasive esophageal surgery (MIES) to evaluate its safety and efficacy as an oncosurgical procedure. Methods: The study included99consecutive patients. Depending on the location of the tumor, either thoracoscopic transthoracic esophagectomy (TTE) in prone position or laparoscopic transhiatal esophagectomy (THE) was planned. 2 field comprehensive nodal dissection were part of both the surgical procedures. Results: 05 patients were excluded, 18 were inoperable and 12 had open surgery. 64 underwent MIES (THE-37, TTE-27), Male: Female-31:33. Nodal Harvest (nodes): THE-14.27, TTE-14.77. Margins (cm): THE-proximal (P) - 6.70, distal (D) -2.51, TTE: (P)-5.41, (D)-5.11. 30 days Morbidity (26): cervical leak-05, left vocal cord palsy-05, tracheostomy-03, respiratory insufficiency-03, aspiration-01, chyle leak-01, exploratory laparotomy-01, cardiac-02, stroke-01, surgical emphysema -01, abdominal wound Infection -03 30 days Mortality (1) –pulmonary embolus. Operative time (minutes): THE-234, TTE-322. Blood loss (ml/patient): THE-265, TTE-380. Hospital stays (days): THE-7.3, TTE-10. Conclusions: 79% of properly selected & evaluated cases underwent MIES, with one Mortality and 26 events of morbidity. 6% required conversion. The procedure detected inoperability in 16% cases. The nodal yield, status of margins, operative time, blood loss and hospital stay indicates that MIES has a future to become a standard of care in the treatment of esophageal cancers.